After 40 years gossypiboma caused spleen abscess - Ivica, Mihovil (Array, 2009)
Abstract: We report a case of spleen abscess cased by foreign body (gossypiboma) after 40 years. After physical examination, laboratory, ultrasonography and CT findings with diagnosis of acute abdomen, 73 years old woman had undergone laparatomy. Operation revealed intraabdominal spleen abscess. Capsulotomy and drainage of the collection was performed before splenectomy. Histological examination showed foreign body material surrounded by chronic inflammation, foreign body-type multinucleated giant cells, extravasated red blood cells and fibroblastic proliferation. From anamnesis we found that woman was operated only once during a life with diagnosis of extrauterine pregnancy, 40 years ago. Spleen abscess caused by gossypiboma after 40 years was never described before. However, diagnosis like this is very well known but rarely published because medical-legal implication. Education, professionalism and cooperation of all persons involved in surgical procedure are very important to prevent accidentally mistakes